The factors that predict success or failure of trial of labor after a previously blow segment cesarean section - Tansengco, Maria Lora G.
General Objective: To determine the factors that predict success or failure of a trial of labor for vaginal delivery among pregnant women in labor with a previous low segment cesarean section. Specific Objectives: 1. To determine whether the following variables are predictive of success or failure of trial of labor after a previous low segment cesarean section. a. maternal age. b. age of gestation. c. gravidity. d. educational status. e. number of previous vaginal delivery/s. f. indication for previous or primary cesarean section. g. cervical dilatation during the previous or primary cesarean section. h. duration of labor prior to primary cesarean section. i. current estimated fetal weight. j. cervical dilatation at start of trial of labor. k. cervical effacement at start of trial of labir. l. bishop score at start of trial of labor. m. nonreassuring fetal heart rate tracing on admission. n. use of oxytocin. o. use of anesthesia during labor. 2. To determine obstetric, demographic, and nonclinical variables that will identify the best outcome for a trial of labor after a previous low segment cesarean section using the logistic regression model than would best predict sucess or failure of vaginal birth after cesarean, while controlling for potential confounders. 3. To devise a risk factor scoring system using the results of logistic regression which will be applied to patients in labor with a previous low segment cesarean section and who are eligible for a trial of labor. STUDY DESIGN: The study employed a prospective, cohort design. SUBJECTS: Three hundred forty one (341) pregnant patients with a previous cesarean section who were admitted at the Philippine General Hospital Obstetric Admitting Section and who fulfilled the following inclusion criteria were included in the study: Patients with known low transverse cesarean section scar, singleton pregnancy, vertex presentation, informed consent. Excluded were the following: pstients with known classical or low vertical cesarean section scar, multiple gestation, malpresentation, more than two uterine scars, previous myomectomy or other surgeries done on the uterine fundus. METHODOLOGY: Information on the factors investigated, or the independent variables, were collected on admission following their agreement to a trial of labor. The data were properly documented in a standardized database form. The patients were followed-up until delivery and classified under either the successful trial of lbor group or failed trial of labor group. Other information on pregnancy and fetal outcome were recorded. The dependent variables are success or failure of trial of labor after a previous cesarean section. MAIN OUTCOME MEASURES; Univariate analysis was performed using the t-test (for quantitative variables) or chi2 (for qualitative variables) to determine which among the individual variables were significant. The odds ratios with a 95% confidence interval were also determined. Multivariate analysis using logistic regression was then used t determine the model that would best predict vaginal birth after a previous cesarian section while contrlling for potential confounders. A risk factor scoring system was constructed based on the results of the logistic regression analysis. RESULTS; Among the 341 patients who underwent trial of labor, 282 (82.7%) underwent successful vaginal birth while 59 (17.3%) underwent emergent repreat cesarean deliveries. Based on the logistic regression analysis, the factors that could predict success or failure of trial of labor for VBAC and their odds ratios are: Estimated fetal weight (OR 0.99, 95% CI 0.998,0.999), fetal heart trace on admission (OR 11.494, 95% CI 5.097, 25,920), number of previous vaginal deliveries (1.43, 95% CI, 0.98, 2.08), and Boshop sore (OR 1.35, 95% CI, 1.19, 1.54). There was no maternal mortality. There were two patients who successfully delivered vaginally with hemorrhagic complications: one was due to uterine dehiscence and another was due to uterine atony. There were two infants born with 1 and 5-minute Apgar scores less than 7 one each from the succesful and failed trial of labor group. CONCLUSIONS: Using the logistic regression model with the best fit, we constrcuted a six-poing scoring system that used the beta-coefficients corresponding to the weights contributed by factors significantly predictive of the outcome of a trial of labor. The four variables found to have a significant association with the outcome are the number of previous vaginal deliveries, estimated fetal weight, Bishop score, and the fetal heart trace. Validation of this clinical tool is warranted in different populations.
Theses--((Master of Science in Epidemiology-Clinical Epidemiology) UPCM
Keywords: Labor complications